2011
DOI: 10.1007/s12306-011-0119-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional results in calcific tendinitis of the shoulder treated with rehabilitation after ultrasonic-guided approach

Abstract: Calcific tendinopathy of the rotator cuff is a chronic disease that mostly in the acute phase compromises the articular function. The aim of this study is to estimate the effectiveness of the ultrasonic-guided percutaneous treatment (UGPT) in association with the rehabilitative treatment. We evaluated 106 patients with calcific tendinopathy, treated by UGPT. They underwent clinical evaluation by a physiatrist at T0 (the same day of UGPT), and were reassessed at follow-up 1 month (T1) after treatment. The asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…The patient's home programme, recommended below the pain threshold, was based on (1) exercises for shoulder lowering and decoaptation to be performed also in common daily activities, (2) assisted and active self-mobilization (recovery of range of motion), (3) isometric strengthening of rotator cuff and deltoid, (4) stretching in elevation, abduction and rotation. 27,28 The programme was tested with the assistance of a therapist. At the end of the morning patients were discharged from the department, with anti-inflammatory drugs on demand and physiatrist programme to be performed in the subsequent month.…”
Section: Extracarementioning
confidence: 99%
See 1 more Smart Citation
“…The patient's home programme, recommended below the pain threshold, was based on (1) exercises for shoulder lowering and decoaptation to be performed also in common daily activities, (2) assisted and active self-mobilization (recovery of range of motion), (3) isometric strengthening of rotator cuff and deltoid, (4) stretching in elevation, abduction and rotation. 27,28 The programme was tested with the assistance of a therapist. At the end of the morning patients were discharged from the department, with anti-inflammatory drugs on demand and physiatrist programme to be performed in the subsequent month.…”
Section: Extracarementioning
confidence: 99%
“…25 Following a specific rehabilitation protocol after the procedure may also result in better outcomes. [26][27][28] Ultrasound-guided needling also showed better results in function restoration and pain relief in the short term than extracorporeal shock wave therapy, both improving clinical outcome and eliminating calcific deposit. 29 The correct selection of patients to be submitted to ultrasoundguided percutaneous treatment is crucial.…”
mentioning
confidence: 95%
“…The case series (n = 264) in this review showed measurable reduction in pain and disability after treatment with ultrasoundguided needle lavage [6,8,10,19]. Yoo et al [9] (n = 30) explored the effects of ultrasound-guided needle lavage with corticosteroid injection on degree of improvement in movement and reduction in calcification size.…”
Section: Evidence For Ultrasound-guided Needle Lavage: Case Seriesmentioning
confidence: 87%
“…Characterized by acute or chronic inflammation around crystal hydroxyapatite on the rotator cuff tendons, this disease usually affects adults older than 30-40 years [5]. The supraspinatus tendon appears to be most susceptible, being affected as much as 80% of the time [6]. The cause of the calcification is not clear [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation